Quality control of some products containing iron available in the local market (Latakia University Journal -Medical Sciences Series, 2023)
Iron supplements are generally available over-the-counter (OTC) and widely prescribed to treat anemia and other disorders. Low iron concentration in the pharmaceutical preparations may lead to treatment failure and increase the severity of the disease. The quality of iron supplements should be monitored to ensure that they contain the same quantity labeled on the packaging.The aim of this study was to monitor the quality of some iron-containing preparations available in the Syrian market, and determine their content of ferrous iron using UV-Visible spectrophotometer at 510nm after forming a colorful complex with the 1.10-Orthophenantroline detector.Routine quality control, content and dissolution tests were carried out on four local companies A, B, C, and D. Ferric iron had also been quantified in the studied samples. Only company A had met the requirements with regard to the external packaging, and all batches conform to pharmacopeia limits related to visual characterizes, except C1(L) tablets that showed obvious deterioration and cracking in the coating layer.All samples passed the uniformity of weight test, and most of them had appropriate hardness and disintegration time less than 30 minutes, except Company C tablets which were the hardest and failed in disintegration test.In terms of content test, all samples met pharmacopeia parameters and contained a small amount of ferric iron, except B1 batch tablets. A and B tablets passed the dissolution test but C tablets failed, and D Capsules did not show any modified-release properties.